2016
DOI: 10.1007/s00408-016-9890-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cell Turnover in the Bronchiolar Epithelium Through the Normal Aging Process

Abstract: We found a decrease in the total number of epithelial cells in the aged mice, which was accompanied by a thinning of the epithelium. These changes reflect a dysregulated tissue regeneration process in the bronchiolar epithelium that might predispose to respiratory diseases in elderly subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…4a,b,d). The reduced club cell proliferation rate that we observed was in agreement with a previous study which found that the percentage of PCNA + proliferating cells fell by 69% between 2 and 24 months of age 43 . Notably, the baseline level of PCNA + cells in young mice in this study was 0.068%, whereas our baseline level of EdU incorporation over 2 weeks in club cells in young mice was 17.7%.…”
Section: Discussionsupporting
confidence: 93%
“…4a,b,d). The reduced club cell proliferation rate that we observed was in agreement with a previous study which found that the percentage of PCNA + proliferating cells fell by 69% between 2 and 24 months of age 43 . Notably, the baseline level of PCNA + cells in young mice in this study was 0.068%, whereas our baseline level of EdU incorporation over 2 weeks in club cells in young mice was 17.7%.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the reduced ciliary beat frequency that was observed in aged versus young mice [ 131 ]. Old mice also have a reduced number of epithelial cells due to increased apoptosis, and resulting in epithelial thinning [ 132 ]. Virus-induced damage of club cells and their subsequent regeneration was similar in young and aged mice, however [ 133 ].…”
Section: Age-associated Changes In Pulmonary Structure and (Immunementioning
confidence: 99%
“…The lower respiratory tract includes the trachea and within the lungs, the bronchi, bronchioles, and alveoli. This system performs or participates in several functions: air conduction, gas exchange, olfaction, and phonation [13][14][15].…”
Section: Pulmonary Cartilagementioning
confidence: 99%
“…On the opposite, other authors affirm that PCNA is the most reliable and versatile of all markers used to analyze cell proliferation [75]. In the past, we have successfully used the immunohistochemical detection of PCNA in studies of cell turnover in lung [76].…”
Section: Identification and Measurement Of Cell Proliferationmentioning
confidence: 99%